Influence of temperature on impedance spectra of thin film of poly(styrenesulfonate) doped poly(3,4 ethylenedioxythiophene) - (:unkn) unknown (American Institute of Physics Inc., 2010)
The temperature dependence of the impedance spectra of PEDOT:PSS thin film have been investigated in the frequency range of 40 Hz-105 Hz. and temperature range 303-473 K. Obtained data reveal that a.c conductivity obeys the relation σac(ω) - Aωs and exponent s is found to decrese by increasing temperature. The obtained results were compared with the prediction of the Quantum Mechanical Tunelling (QMT) and Correlated Barrier Hopping (CBH) models. The analysis showed that the dominant conduction mechanism in PEDOT:PSS film is multihopping for frequency region 40Hz-7kHz at all temperatures, for region of 7kHz-100kHz, the small polaron tunneling model is the dominant conduction mechanism in film which contributes to the ac conductivity. © 2009 American Institute of Physics.
Keywords: Ac conductivity; Capacitance; Impedance spectra